1984
DOI: 10.1016/s0022-5347(17)49941-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Female Stress Incontinence with Imipramine

Abstract: The results of a clinical study of conservative treatment of women with stress incontinence are presented. A daily dose of 75 mg. imipramine hydrochloride was given for 4 weeks. Special attention was paid to the effects of imipramine on the functional urethral length and maximum urethral closure pressure. A total of 21 women (71 per cent) stated that they were continent after treatment with imipramine, while 9 (29 per cent) did not improve and treatment was stopped. According to our results, imipramine extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
6

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 17 publications
1
13
2
6
Order By: Relevance
“…Cardiotoxicity in the form of arrhythmias is also known to occur. A noncontrolled trial by Gilja et al [54] in 30 women with SUI treated with imipramine for 4 weeks showed subjective continence in 21 (71%). Lin et al [55] found that 60% of the patients treated with imipramine improved by more than 50% (based on pad weight).…”
Section: Imipraminementioning
confidence: 99%
“…Cardiotoxicity in the form of arrhythmias is also known to occur. A noncontrolled trial by Gilja et al [54] in 30 women with SUI treated with imipramine for 4 weeks showed subjective continence in 21 (71%). Lin et al [55] found that 60% of the patients treated with imipramine improved by more than 50% (based on pad weight).…”
Section: Imipraminementioning
confidence: 99%
“…These data show that estrogens do not appear to be an effective treatment for stress urinary incontinence. Although efficacy of imipramine has been suggested in open studies [69,70], no randomized clinical trial supports its clinical use. Propranolol, clenbuterol and methoxamine were reported to improve stress incontinence in studies with low level of evidence [71][72][73].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Son utilisation dans le traitement de l'IUE se justifie par une augmentation de la PCUM, qui passe de 34 à 48 mm Hg (p > 0,05) et par une amélioration subjective de la symptomatologie urinaire d'après l'étude de Gilja [16]. Son utilisation dans le traitement de l'IUE se justifie par une augmentation de la PCUM, qui passe de 34 à 48 mm Hg (p > 0,05) et par une amélioration subjective de la symptomatologie urinaire d'après l'étude de Gilja [16].…”
Section: L'imipramineunclassified